THE RIGHT TO LEGAL REPRESENTATION AT STATE EXPENSE FOR CHILDREN IN CARE AND CONTACT DISPUTES – A DISCUSSION OF THE SOUTH AFRICAN LEGAL POSITION WITH LESSONS FROM AUSTRALIA - Marita Carnelley (Obiter, 2021)
The article discusses the right of children to legal representation at state expense in family disputes in South Africa as provided for in section 10 of the Children’s Act 38 of 2005 and section 28(2)(h) of the Constitution. Certain aspects are highlighted: the applicant applying for legal representation; the requirements for an appointee; the appointment criteria; duties and responsibilities of the appointee as well as the funding for such appointment. The South African legal principles are compared with the equivalent Australian provisions relating to the Independent Children’s Lawyer. The article concludes with some recommendations for lacunae identified in the South African system in light of the Australian experience.